A Campus Lake as the Centerpiece for a Semester‐Long Hydrology Course. Issue 1 (20th June 2019) - Dripps, Weston
Abstract : Core Ideas: A campus lake serves as the unifying thread for a watershed hydrology course. All field, laboratory, and classroom components are explicitly linked to the lake. The course provided needed data for tracking the ongoing management of the lake. Using the lake promoted a sense of personal environmental responsibility for students. In recent years there have been concerted efforts among water science educators to increase the number and quality of interactive classroom, field, and lab experiences in undergraduate water resource courses. This article reviews the transformation of a traditional lecture‐based hydrology course with a global emphasis to a field‐based, integrated watershed hydrology course with a local emphasis. An 11.3‐hectare (28‐acre) campus lake serves as the overarching and unifying basis for the entire course, with each field exercise, laboratory, and class lecture centered on quantifying the lake's water budget. The lake affords the opportunity to teach the science of hydrology by focusing on understanding and quantifying the natural physical processes that comprise the lake's water budget while considering local human impacts on this budget. Making the campus lake the centerpiece for this course (1) provides a unifying thread that links the field, laboratory, and classroom experience into an iterative, integrative whole; (2) grants students easy, convenient access to a field site that affords ample opportunities for field‐based, experiential learning, class exercises; (3) gives the university necessary hydrologic data for tracking improvements to the ongoing management and restoration of the lake; and (4) helps promote a sense of personal environmental responsibility as students explore the linkages between the university's practices and the impact of these practices to the lake ecosystem.